Report templates for evaluability assessment (Methods Lab, 2015)
An evaluability assessment aims to assess the extent to which, and how best, a project can be evaluated in a reliable and credible fashion. These templates are intended to help anyone conducting an evaluability assessment to structure the final report. This tool was developed by Anne Buffardi and Bronwen McDonald for use in Methods Lab projects. It accompanies The Methods Lab publication ‘Evaluability assessment for impact evaluation: guidance, checklists and decision support’.